The Relevance of the Theory of Legal Change According to Ibnu Qayyim Al-Jauziyyah in Legal Products by Fatwa DSN-MUI Indonesia - Muhamad Izazi Nurjaman; Doli Witro (Institut Agama Islam Negeri Palangka Raya, 2021)
The study described the relevance of the theory of legal change according to Ibnu Qayyim al-Jauziyyah to the legal product of the fatwa DSN-MUI (Fatwa National Sharia Board-Indonesian Council of Ulama) in Indonesia. It used a qualitative research method with a literary approach. The conclusions showed that the relevance of the theory of legal change proposed by Ibn Qayyim al-Jauziyyah has been applied explicitly in every legal product of the fatwa DSN-MUI in Indonesia. That seen in every legal product, always give the way for future changes following the needs and problems faced. Changes to Islamic legislation products have significant differences. On laws and regulations and judges' decisions, new legal products will cancel or revoke the previous legal. And, for the legal product of a fatwa from the National Syari'ah Board (DSN-MUI), the newly legal product will complete the previous one. However, legal changes will always occur in the context of providing legal certainty, accompanied by the level of benefit for people's lives.